2016
DOI: 10.1080/1067828x.2015.1049394
|View full text |Cite
|
Sign up to set email alerts
|

Anger and Its Association with Substance Use Treatment Outcomes in a Sample of Adolescents

Abstract: Anger is a common affective experience, yet it is relatively understudied in the substance use treatment literature. This study explored anger as a predictor of treatment outcomes in a large sample of adolescents. Data were extracted from the Drug Abuse Treatment Outcome Study for Adolescents (DATOS-A). An anger profile was created based on adolescents’ pre-treatment responses to four items assessing history of temper outbursts and aggression. Individuals were classified as High Anger (n = 506) and Normal/Low … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 26 publications
0
15
0
6
Order By: Relevance
“…The studies were carried out in the United States, Brazil, Turkey, Saudi Arabia, Canada, Italy, Finland, and Hungary. The STAXI scales were used in 10 studies 18,26,[40][41][42][43][44][45][46][47][48][49] and the BPAQ in the other two studies. 26,40 Substance users had higher anger levels compared to non-users ( Figure 2) (SMD = 2.151; 95% confidence interval [95%CI] 1.16 to 3.14, p o 0.001).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The studies were carried out in the United States, Brazil, Turkey, Saudi Arabia, Canada, Italy, Finland, and Hungary. The STAXI scales were used in 10 studies 18,26,[40][41][42][43][44][45][46][47][48][49] and the BPAQ in the other two studies. 26,40 Substance users had higher anger levels compared to non-users ( Figure 2) (SMD = 2.151; 95% confidence interval [95%CI] 1.16 to 3.14, p o 0.001).…”
Section: Resultsmentioning
confidence: 99%
“…Several factors need to be considered in interpreting these results, such as: the relationship of anger with psychiatric comorbidities, traumatic stress during childhood and adolescent development, personality and temperament features; our understanding of the neurobiological apparatus of emoticons and its relationship with neuroadaptation of the brain secondary to PSU; the type of substance used; the timing of anger measurement -whether during active use or abstinence/withdrawal; and the frequency of use. 33,50,51 Drug users appear to experience anger more often and more intensely than non-users. This may be attributable to several factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, social isolation, chronic quarantine measures, and the pandemic outbreak itself have shown to be associated with increased emotional distress such as depression, anxiety, anger, irritability, and fear ( Lai, Shih, Ko, Tang, & Hsueh, 2020 ). People are more prone to relapse in these conditions, though experiencing a long-term a n ( Serafini, Toohey, Kiluk, & Carroll, 2016 ). Compounding this scenario, group-based effective therapies that were held before the start of the pandemic to support people with SUD with emotional and psychological distress have been canceled due to the restrictions imposed.…”
Section: Introductionmentioning
confidence: 99%
“…[11] Serafini et al showed that high anger was associated with a greater likelihood of experiencing delirium tremens, relapsing on drugs due to alcohol use, having difficulty controlling temper and behavior, and being arrested for attacks on persons. [12] Eftekhari et al suggested that expression of anger and avoidant coping are independent risk factors for substance use in incarcerated adolescents. [13]…”
Section: Introductionmentioning
confidence: 99%